Indigenous Knowledge for Development Program : Two Years Down the Road - World Bank (Washington, DC, 2012)
While most African nations adopted economic policies, with a view to modernize society, and transform the productive sectors, indigenous knowledge - that could have supported this process, or offered alternative perspectives - was often relegated. However, the 1992 Rio Earth Summit, through the notion of sustainable development, catapulted these practices to the forefront of the development discourse. Policymakers are highlighting the critical role of indigenous knowledge in the development process : from the Global Knowledge Conference, Toronto 1997, to the Indigenous Knowledge (IK) for Development Initiative, headed by the World Bank, in collaboration with the United Nations. The note briefly reviews the progress achieved through the IK Development Initiative in disseminating information; facilitating information exchange among developing communities; applying IK in the development process; and, establishing partnerships. Challenges include intensified efforts to mainstream IK into the development process; greater donor involvement, and active participation; facilitating interactive exchanges by establishing communities of practice through various fora; and, forming local alliances to facilitate empowerment.